A Method for the Delimitation of an Equidistant Boundary Between Coastal States on the Surface of a Geodetic Ellipsoid - Carrera, Galo (The International Hydrographic Review, 2015)
The mathematical apparatus available to geodesists for the task of positioning on the surface of a reference ellipsoid is used to develop a new maritime delimitation method. The method is based on two combinatorial algorithms and requires only the geodetic coordinates of the baseline points of at least two coastal States. The end result of this method is a set of turning points from which the boundary can be drawn.